Growth and enzymatic responses of phytopathogenic fungi to glucose in culture media and soil - Costa, Beatriz de Oliveira [UNESP]; Nahas, Ely [UNESP] (Sociedade Brasileira de Microbiologia, 2012)
The effect of inoculation of Aspergillus flavus, Fusarium verticillioides, and Penicillium sp. in Dystrophic Red Latosol (DRL) and Eutroferric Red Latosol (ERL) soils with or without glucose on the total carbohydrate content and the dehydrogenase and amylase activities was studied. The fungal growth and spore production in culture medium with and without glucose were also evaluated. A completely randomized design with factorial arrangement was used. The addition of glucose in the culture medium increased the growth rate of A. flavus and Penicillium sp. but not of F. verticillioides. The number of spores increased 1.2 for F. verticillioides and 8.2 times for A. flavus in the medium with glucose, but was reduced 3.5 times for Penicillium sp. The total carbohydrates contents reduced significantly according to first and second degree equations. The consumption of total carbohydrates by A. flavus and Penicillium sp. was higher than the control or soil inoculated with F. verticillioides. The addition of glucose to soils benefited the use of carbohydrates, probably due to the stimulation of fungal growth. Dehydrogenase activity increased between 1.5 to 1.8 times (p <0.05) in soils with glucose and inoculated with the fungi (except F. verticillioides), in relation to soil without glucose. Amylase activity increased 1.3 to 1.5 times due to the addition of glucose in the soil. Increased amylase activity was observed in the DRL soil with glucose and inoculated with A. flavus and Penicillium sp. when compared to control.
Keywords: Fusarium verticillioides; Aspergillus flavus; Penicillium sp; dehydrogenase; amylase